THE NIGERIAN STATE AND THE RESPONSIBILITY OF HISTORIANS - Isah Mohammed Abbass (European Scientific Journal, ESJ, 2014)
Since the evolution of the Nigerian State, failures in economic, political and social realms have been multifaceted and multi-dimensional. Historical trajectory in these series of failures has not been explicit. In certain perspectives however, these state failures might have been over-looked or over-exaggerated. Hence, what seems to be a turning point in the history of the Nigerian State might have been discussed, written and agreed by many Nigerian historians. Different points of controversial views, either conservative or radical, have been expressed with, of course, harmony and agreement within the community of historians. This paper examines the responsibility of historians, irrespective of their orientations, personalities and analytical methods, in constructing the faulty, ethnocentric and historical account of the past and contemporary Nigerian State. The need, therefore, to continue producing and reproducing professionals with ethical responsibility and historical irreducibility of the Nigerian political diversity becomes imperative for the stability of the Nigerian State. It is contended that the Nigerian modern state must be analyzed by historians in the light of the tedious, lengthy and protracted passage of time and with the application of the historical trajectories and distinct historicity of the evolution and development of the Nigerian State.